Cytokines in Thyroid-Associated Ophthalmopathy - Pengbo Zhang; Huang Zhu (Journal of Immunology Research)
Thyroid-associated ophthalmopathy (TAO), also known as thyroid eye disease (TED) or Graves’ orbitopathy (GO), is a complex autoimmune condition causing visual impairment, disfigurement, and harm to patients’ physical and mental health. The pathogenesis of TAO has not been fully elucidated, and the mainstream view is that coantigens shared by the thyroid and orbit trigger remodeling of extraocular muscles and orbital connective tissues through an inflammatory response. In recent years, cytokines and the immune responses they mediate have been crucial in disease progression, and currently, common evidence has shown that drugs targeting cytokines, such as tocilizumab, infliximab, and adalimumab, may be novel targets for therapy. In this review, we summarize the research development of different cytokines in TAO pathogenesis in the hope of discovering new therapeutic targets.